The Algorithmic Architect: How AI is Redefining Hospital Design - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The Algorithmic Architect: How AI is Redefining Hospital Design The integration of Artificial Intelligence (AI) into healthcare is rapidly moving beyond...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning